Iron-mediated tissue damage in acquired ineffective erythropoiesis disease: It's more a matter of burden or more of exposure to toxic iron form?. (March 2022) - Pilo, Federica; Cilloni, Daniela; Della Porta, Matteo Giovanni; Forni, Gian Luca; Piperno, Alberto; Santini, Valeria; Angelucci, Emanuele
Highlights: Iron is an essential metal in cell life, but when in excess produces reactive oxygen species (ROS) that are cytotoxic, especially in ineffective erythropoiesis diseases. Different organs have a different capacity to respond to iron-mediated toxicity, suggesting that toxicity thresholds are disease-specific, tissue-specific, and patient-dependent. Consistent preclinical and clinical evidences describe how tissue damage is related to the duration of exposure of the various tissues to ROS in a non-dose-dependent manner. The understanding of the importance of the exposure to free iron in inducing iron-related damage rather than the consolidated concept of accumulation has urged the scientific community to design study protocols in which iron chelation has the primary objective of reducing organ exposure to ROS at an early stage, in order to avoid or at least delay the development of organ damage. Abstract: Iron is essential in cellular life, however, when in excess, it favors the production of reactive oxygen species (ROS) that, when overwhelm the physiological cellular antioxidant system, produce an oxidative stress state leading to cellular damages and organ failure. What is not yet completely clear is whether the damage is related more to the amount of iron or to the duration of exposure to ROS. Various cellular pathways are sensitive to the detrimental action of ROS in a non-dose-dependent manner. In addition, different organs have a different capacity to respond to iron-mediated toxicity, suggesting that the toxicity thresholds are disease-specific and patient-dependent. The aim of this article is to review the recent understanding of the concept of exposure to free iron-mediated damage, comprehending the need to design protocols in which reducing organ exposure to ROS is the primary objective in order to prevent or delay the development of organ damage.